Gambaran Tingkat Pengetahuan Deteksi Dini COVID-19 di Bandara pada Petugas Kantor Kesehatan Pelabuhan Kelas IV Yogyakarta - Iriyanti, Mutia; Martini, Martini; Yuliawati, Sri; Saraswati, Lintang Dian (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Disease prevention activities at the entrance are a form of implementing IHR 2005. The COVID-19 pandemic has increased disease surveillance at airports to prevent disease from spreading in the region, one of which is early detection. In carrying out these activities, the knowledge of officers is very important, especially regarding the early detection of COVID-19 at the airport. The purpose of the study was to describe the level of knowledge of early detection of COVID-19 at the airport for the Port Health Office Class IV Yogyakarta officers. This study uses a descriptive observational method with a cross sectional design. The research population is Port Health Office Class IV Yogyakarta officers who duty at the airport, based on criteria the number of samples was 40 respondents. Data were collected using a questionnaire, which was then analyzed using a cross table. Port Health Office Class IV Yogyakarta officers who duty at the airport have less knowledge about the early detection of COVID-19 as many as 27 people (67.5%). Officers with a low level of knowledge about the early detection of COVID-19 are in the early adult age group (21-40 years), female, undergraduate / diploma IV, and working period < 3 years. Regular training is needed to improve the knowledge and skills of officers. Keywords: Knowledge, early detection of COVID-19, Airports, Port Health Officer